Study of 18β glycyrrhetinic acid for the prevention of progression of diabetes induced neuropathy in laboratory animals (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Diabetes is a metabolic disease that is associated with oxidative stress and the dysfunction of mitochondria. Long-term diabetes may cause different associated complications. One of the most common complications of diabetes mellitus is neuropathy. The present study aimed to investigate the possible neuroprotective effects of 18β glycyrrhetinic acid (GA), the metabolite of glycyrrhizic acid, which is the main active component commonly used in traditional Chinese medicine on oxidative damage and the sciatic nerve of diabetes-induced neuropathy in laboratory animals. Diabetes was induced in male Wistar rats (200–260 g) by injecting a single dose of nicotinamide (110 mg/kg, intraperitoneally) and streptozotocin (STZ) (55 mg/kg, intraperitoneally). The rats were divided into six groups. Pregabalin (10 mg/kg, p.o.) and 18β GA (50, 100, and 200 mg/kg, p.o.) were administered daily after four weeks of nicotinamide-STZ injection to the rats of groups III to VI respectively for four weeks. Various behavioral (heat and mechanical hyperalgesia, allodynia, etc.), hemodynamic and biochemical parameters were investigated, and the histological examination of the sciatic nerve was carried out. In the present study, the 18β GA (100 and 200 mg/kg) significantly (p < 0.01, p < 0.001) increased in the tail withdrawal latency and increased in paw withdrawal threshold, and increased in systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure. Furthermore, 18β GA (100 and 200 mg/kg) significantly (p < 0.01, p < 0.001) restored altered blood glucose level, total protein, antioxidant status, and histological abnormalities. Pregabalin (10 mg/kg) showed a maximum protective effect, but a low dose of 18β GA (50 mg/kg) was not enough to show the protective activity in diabetic rats. In most of the tests, non-significant differences were observed between the control and 18β GA 200 mg/kg groups. Moreover, 18β GA lowers the inflammation and demyelination in sciatic nerves. Beyond its antioxidant role possessed neuroprotective effect via modulation of endogenous enzymes in nicotinamide-STZ induced diabetic in rats.